Mineral nutrition and yield of sesame in the Ganges tidal floodplain soil (Bangladesh Journal of Agricultural Research, 2008)
A field trial was conducted in the saline region of Satkhira District (AEZ 13) to investigate the mineral nutrition and yield of four varieties of sesame in kharif-1 season of 2002. The varieties were BARI Til-2, BARI Til-3, T-6 and local (red). The soil and irrigation water salinity at sowing were 2.63 and 2.01 dS m-1, respectively. Among the varieties, the T-6 produced the highest seed yield (1.66 t/ha) and BARI Til-3 (0.71 t/ha) did the lowest. The maximum 1000-seed weight (2.66 g) was recorded in T-6 variety and the minimum was (2.27 g) in local (red) variety. The N, P, K, Zn, and S concentrations of seeds or stovers of different varieties were statistically identical. The uptake of these elements also did not vary with varieties.DOI: http://dx.doi.org/10.3329/bjar.v32i3.540Bangladesh J. Agril. Res. 32(3) : 387-391, September 2007